The decline of fisheries on the Madeira River, Brazil: The high cost of the hydroelectric dams in the Amazon Basin - Santos, Rangel E.; Pinto‐Coelho, Ricardo M.; Fonseca, Rogério; Simões, Nadson R.; Zanchi, Fabrício B. (Fisheries management and ecology, 2018)
Despite being considered beneficial by providing a clean and renewable source of energy, the construction of hydroelectric dams has extremely negative implications for Amazonian fisheries. This study investigated the impacts of the Santo Antônio and Jirau hydroelectric dams on the fishery stocks of the Madeira River. This investigation was based on fish catch data from the Z‐31 fishing colony, located in the municipality of Humaitá, in Amazonas State, Northern Brazil. Data were collected daily and provided information on the date of return from each trip, the fish species targeted, and the total catch (kg) between January 2002 and September 2017. The results indicated reductions of 39% in the mean annual catch and 34% in the mean monthly catches. These results highlight the high price paid by local fish communities for the development of hydroelectric power in the Amazon basin.